Imagined communities : reflections on the origin and spread of nationalism - Anderson, Benedict R. O'G. (Benedict Richard O'Gorman), 1936-2015 (London : Verso, 2016)
The defining, best-selling book on the history, origins and development of nationalism.
Introduction -- Cultural roots -- The origins of National consciousness -- Creole pioneers -- Old languages, new models -- Official nationalism and imperialism -- The last wave -- Patriotism and racism -- The angel of history -- Census, map, museum -- Memory and forgetting -- Travel and traffic: on the geo-biography of Imagined communities.
First published: Verso, 1983.
Includes bibliographical references (pages 230-233) and index.
ENH
Keywords: Nationalism -- History; English language; History